Functional outcomes of soft palate free flap reconstruction following oropharyngeal cancer surgery. Issue 9 (September 2021) - Melan, Jean-Baptiste; Philouze, Pierre; Pradat, Pierre; Benzerdjeb, Nazim; Blanc, Jacques; Ceruse, Philippe; Fuchsmann, Carine
Abstract: Introduction: The objective of this study was to assess the impact of surgical resection and free flap reconstruction of soft palate cancer on speech, swallowing and quality of life, and to identify the factors influencing functional outcomes and quality of life. Material and methods: Patients treated with surgical resection of squamous cell carcinoma and free-flap reconstruction of the soft palate were reviewed at least 12 months after surgery. Speech was assessed using the Hirose intelligibility scoring system, nasalance scoring, GRBAS scoring and the Voice Handicap Index 30 (VHI30) questionnaire. Swallowing was assessed by fiberoptic endoscopy and the Deglutition Handicap Index (DHI). Quality of life was assessed using EORTC QLQ-C30 and QLQ-H&N35 questionnaires. Results: 29 patients were included. Speech outcomes were satisfactory, demonstrating normal or slightly below normal speech intelligibility in 75.9% of the patients, moderate or no rhinolalia in 72.4% of the patients and mean overall VHI30 scores indicative of slight or no handicap in 86.2% of the patients. Swallowing outcomes were satisfactory, with mean overall DHI scores indicative of slight or no handicap in 82.8% of the patients. Patient quality of life was preserved as demonstrated by mean quality of life and functioning scales scores all superior to 80%. Conclusion: The sequelae arising from surgical resection and free-flap reconstruction of soft palate cancer are tolerable, involving slight handicap in terms of speech and swallowing and relatively little impact on quality of life.